Pointed Arch in Islamic Architecture Between Intentional innovation & spontaneous aim - Kabila Fares Al - Maliki (Iraqi Journal of Architecture and Planning, 2009)
Arch is founded in Islamic Arabic Architecture in many different Buildings,for aethetical and functional purposes that made this Arch one of its symbols, parallelwith it, so the study of this Arch is very important.Many studies took care of this arch, pointed arch with four centers that it isIslamic Arab innovation comparative with all other kinds of arches.We don't know why this arch is specially innovated & used in Islamic ArabArchitecture? What its relationship with pointed Arch by two centers? What causesbehind this innovation?This study aim to search in many concepts explain the innovation of thispointed Arch (with four centers) analytically to discover the beginnings, causes for itsappearance, styles within the unity of Islamic spirit, so it studied Arch Philosophical,its history expressionism, aesthetical values, to be contents of this research to discoverits hidden, answering many questions, inquiring about intention of this Arch or itsspontaneous ? Was it related to aesthetical values, philosophical, ideological, orothers? While pointed Arch with two centers more powerful structurally than pointedArch with four centers, but it was more important and more employment in IslamicArab Architecture.